Lynde Dupuy McCormick papers - McCormick, Lynde Dupuy, 1895-1956.
Correspondence, reports, notes, scrapbooks, clippings, printed matter, photographs, and other papers relating chiefly to McCormick's duty as Supreme Allied Commander Atlantic. Includes trip reports and subject files relating to the countries of the North Atlantic Treaty Organization.
U.S. naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: North Atlantic Treaty Organization; Supreme Allied Commander Atlantic; Sea-power -- Europe; Sea-power -- United States; Security, International; World politics -- 1945-1989.; Europe -- Foreign relations -- United States; United States -- Foreign relations -- Europe; Naval officers